2021
DOI: 10.1002/ardp.202000449
|View full text |Cite
|
Sign up to set email alerts
|

In vivo‐ and in silico‐driven identification of novel synthetic quinoxalines as anticonvulsants and AMPA inhibitors

Abstract: The lack of effective therapies for epileptic patients and the potentially harmful consequences of untreated seizure incidents have made epileptic disorders in humans a major health concern. Therefore, new and more potent anticonvulsant drugs are continually sought after, to combat epilepsy. On the basis of the pharmacophoric structural specifications of effective α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) antagonists with an efficient anticonvulsant activity, the present work reports the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Synthetic route of target compounds C1 – C14 in this work was demonstrated in Scheme 1 . 1-(Chloromethyl)-4-methoxybenzene and 3,4,5-trimethoxyaniline were reacted to perform the nucleophilic substitution 21 , 22 , and an acylation reaction was nextly started to obtain the amide intermediates B1 – B3 . These amide intermediates were reacted with carbon disulphide and secondary amines in the presence of potassium hydroxide to afford compounds C1 – C14 .…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic route of target compounds C1 – C14 in this work was demonstrated in Scheme 1 . 1-(Chloromethyl)-4-methoxybenzene and 3,4,5-trimethoxyaniline were reacted to perform the nucleophilic substitution 21 , 22 , and an acylation reaction was nextly started to obtain the amide intermediates B1 – B3 . These amide intermediates were reacted with carbon disulphide and secondary amines in the presence of potassium hydroxide to afford compounds C1 – C14 .…”
Section: Resultsmentioning
confidence: 99%
“…The control group received subcutaneous PTZ solution (in PEG-200) in the posterior midline of the mice, and the onset and severity of convulsion were noted. 42 3.2.4. Rotarod Neurotoxicity Test.…”
Section: (5-benzothiazol-2-yl-2-methoxy-phenoxy)-acetic Acid Ethyl Es...mentioning
confidence: 99%
“…49 This molecular docking study was performed using the default protocol associated with the glide module of the Schrodinger modelling suite. [50][51][52] Results showed that compound 29 was appropriately oriented in the active site of SARS-CoV-2 M pro protein with a signicant docking score (À7.45 kcal Mol À1 ) and displayed three hydrogen binding interactions with amino acids Gly143, Cys145, and Glu166 as depicted in Fig. 5A and B.…”
Section: Computational Investigationsmentioning
confidence: 99%